Pengaruh Storytelling Terhadap Berbicara Siswa Subtema 3 Bahasa Indonesia Kelas V SDI Al-Washoya Ngoro Jombang - Widyaningrum, Wahyu; Kamidjan; Fitra Raharja, Hawwin (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
This study aimed to determine the effect of the storytelling learning model on students' speaking skill in sub-theme 3; Indonesian Language Competence for grade V at Al-Washoya Ngoro Islamic Elementary School, Jombang. This research used a quantitative research design with experimental research while using one group pre-test and post-test. The population in this study were all students of grade V of Al-Washoya Ngoro Islamic Elementary School which has 15 students. The sample used was the fifth grade students, totaling 15 students who will be experiment class and will be given a storytelling learning model. Based on the data result from pre-test and post-test, it was shown that the students' speaking skills by using storytelling learning model get the sig value of 0.000 <0.05. This result illustrated the effect of the storytelling learning model on students' speaking skills of grade V students at Al-Washoya Ngoro Islamic Elementary School, Jombang for academic year of 2019-2020.